Anonymous money, moral sentiments and welfare - Vesa Kanniainen; Jenni Pääkkönen (Center for Economic Studies and ifo Institute (CESifo), 2004)
Some markets are prone to develop shadow transactions for the purpose of tax avoidance. Moral sentiments control the allocation of consumers between the legal and illicit markets. Such sentiments include self-esteem and social disapproval. The market solution leads to fiscal externality resulting from tax avoidance and highlights the conflict between private opportunism and collective values. Shadow markets may, however, enhance consumer welfare by limiting the pricing power of firms and by controlling tax collection. The paper develops a model of endogenous segmentation of markets between moral and immoral behavior. The legal producer can price the self-esteem of honest people, who can blackmail the legal producer with their option of visiting the illicit market. The model has implications for monetary economics: moral sentiments, tax rates, illegal transactions, and probability of being caught become relevant for the demand for money.
Keywords: D43; L13; H26; E41; D69; 330; moral sentiments; shadow economy; welfare; Ethik; Schattenwirtschaft; Wohlfahrtseffekt